Análise das condições socioeconômicas e culturais de alunos de três escolas municipais de Medianeira/PR a partir dos questionários contextuais do SAEB - Barbiero, Ana Carolina Neumann (2022)
The Basic Education Development Index (initials IDEB in Portuguese), composed of the students’ passing rate and their performance in public and private schools (Federal, State and Municipal), in Portuguese and Mathematics tests run to students in the final years of basic education, is used as a quality parameter of national basic education. Besides the tests, contextual questionnaires are also applied to each school segment (principals, teachers and students). This research aims to analyse the socioeconomic and cultural conditions of students in their initial stage of Elementary School in the town of Medianeira/PR, from the three schools with the lowest IDEB, using the SAEB contextual questionnaires. The theoretical references adopted throughout this final paper are based on the studies developed by Bonamino and Franco (1999); Demo (2010); Freire (2018); Libaneo (1998); Mészáros (2008); Paro (2001, 2014, 2018); Sander (2007); Werle (2011, 2014); Werle et al. (2012) focused on themes like large scale evaluation, school management and quality of education that contributed to the theoretical-conceptual basis of this research. In the study, the contextual questionnaires of the students participating in the SAEB in 2019 of the three schools with the lowest IDEB available on the website of the National Institute of Educational Studies and Research Anísio Teixeira (initials INEP in Portuguese) were analysed, based on the following problem: What are the similarities in the contextual questionnaires at a municipal level, among the three schools with the lowest results in the IDEB in the town of Medianeira/PR? Therefore, a bibliographic research was carried out between the results of the three schools and the IDEB at a municipal level, with a descriptive character permeated by a qualitative-quantitative analysis. The research organization is segmented into four chapters in which we present the attributions of the State Reform in school management in Brazil, the constitution of large-scale evaluation policies, the methodology adopted in the research and the data analysed by the contextual questionnaires applied in 2019 by the SAEB. Among the observed coefficients, low-educational levels of families, the lack of incentive, the scarce technological conditions inside the residences, in addition to some educational factors of the students, such as the failure rates and the lack of autonomous reinforcement of school contents, stood out.